Extreme Wild Card Poker. Issue 4 (1st October 2016) - Fiedler, Ashley; Maasz, Carlie; Meirose, Monta; Spicer, Christopher
Summary: Rankings of hands in traditional five-card poker are based on the relative frequency of each type of hand occurring. When wild cards are added to the standard deck, these rankings can go awry quite quickly. In this paper, wild card poker is taken to the extreme. We find the minimum number of wild cards needed to ensure five-of-a-kind is the most common hand.